SURVEY ON PROCALCITONIN LEVELS AND STRATIFICATION OF PROCALCITONIN LEVELS AMONG 3 GROUPS OF PATIENTS WITH FEVER CAUSED BY SEPSIS, DENGUE FEVER, AND PARASITES (Vietnam Journal of Community Medicine, 2026)
Objective: Survey on procalcitonin levels and stratification of procalcitonin levels among groups of patients with fever caused by sepsis, dengue fever, and parasites.Subjects and methods: This study included 275 patients with fever ≥ 38°C diagnosed with sepsis (137 cases), dengue fever (108 cases), and parasitic infections (30 cases) who were hospitalized at Le Van Thinh Hospital and Cho Ray Hospital from November 2024 to October 2025. The study design was a descriptive cross-sectional study. PCT concentrations were measured using a Beckman Coulter DxI 800 machine.Results: The average age of the septicemia group was 64.16; the dengue fever group was 27.58; and the parasitic group was 38.32 (p < 0.001); there was no significant difference between male and female genders in the three groups (p = 0.595). The highest PCT concentration was in the septicemia group, followed by the parasitic group and the dengue fever group, with statistically significant differences between the groups (p < 0.001). In PCT concentration stratification, the majority of dengue fever and parasitic groups were in the lowest stratum (below 0.5 ng/ml): 69.4-77%; conversely, the septicemia group had very high PCT concentrations in the ≥ 2 ng/ml stratum (65%).Nồng độ và phân tầng PCT ở các nhóm bệnh nhân nhiễm khuẩn huyết, sốt xuất huyết và ký sinh trùng giúp lâm sàng có thể nhận định ngay từ đầu để có chỉ định trong chẩn đoán sớm và điều trị đặc hiệu, kịp thời cho bệnh nhân.Conclusion: The concentration and stratification of PCT in groups of patients with sepsis, dengue fever, and parasitic infections help clinicians make early assessments, leading to timely and specific diagnosis and treatment.
Keywords: Sepsis, dengue fever, parasites, procalcitonin (PCT).